1995
DOI: 10.1136/oem.52.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Manual handling activities and risk of low back pain in nurses.

Abstract: Objective-To investigate the risk factors for low back pain in hospital nurses, with particular emphasis on the role of specific nursing activities. Methods-A cross sectional survey of 2405 nurses employed by a group of teaching hospitals was carried out. Self administered questionnaires were used to collect information about occupational activities, non-occupational risk factors for back symptoms, and history of low back pain. Results-The overall response rate was 69%. Among 1616 women, the lifetime prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
275
3
7

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(310 citation statements)
references
References 17 publications
25
275
3
7
Order By: Relevance
“…These factors can be aggregated into a smaller number of categories [9] including biomechanical factors (regular lifting, exposure to vibration, physically demanding jobs, bending and twisting, pushing and pulling heavy loads, awkward posture) [2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20], psychological/psychosocial factors (job satisfaction, local support in the workplace, depression, job control, stress) [2,7,9,16,[19][20][21][22][23][24][25] and individual risk factors (sedentary lifestyle, age, smoking, gender, obesity, poor general health, marital status, pregnancy) [2,7,9,12,13,20,21,23,[26][27][28][29][30][31]. Past studies have investigated many of these factors and their relationship to LBP.…”
Section: Introductionmentioning
confidence: 99%
“…These factors can be aggregated into a smaller number of categories [9] including biomechanical factors (regular lifting, exposure to vibration, physically demanding jobs, bending and twisting, pushing and pulling heavy loads, awkward posture) [2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20], psychological/psychosocial factors (job satisfaction, local support in the workplace, depression, job control, stress) [2,7,9,16,[19][20][21][22][23][24][25] and individual risk factors (sedentary lifestyle, age, smoking, gender, obesity, poor general health, marital status, pregnancy) [2,7,9,12,13,20,21,23,[26][27][28][29][30][31]. Past studies have investigated many of these factors and their relationship to LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses' work motivation has proven to be an important factor for their intent to work [38] and job satisfaction [39]. Detection of the factors that increase and decrease the motivation levels of shifts were longer than twelve hours, so the nurses on night shifts can make considerable mistakes while performing their duties in hospitals [26].…”
Section: Temporal Aspect Of Job Demandmentioning
confidence: 99%
“…There are numerous reports [7,[16][17][18][19][20][21] on the effect of educational interventions for preventing lumbago among health care practitioners carrying out patient-handling tasks. However, little information is available on the effect of educational intervention for physical therapists.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have pointed out the significance of patient-handling tasks, such as transferring patients, as the cause of lumbago [2,[10][11][12][13][14][15], and a large number of reports on the effect of educational intervention on the prevention of lumbago resulting from patient-handling tasks among nurses and nursing students have been published. Yassi et al [7] reported that physical load to low back during patient-handling task was reduced by technical and concentrated training as well as by introducing the appropriate supporting equipment for the task [16]. The effectiveness of educational intervention for lumbago prevention among nurses working in hospitals has also been reported [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation